IMPLEMENTATION OF EARLY BREASTFEEDING INITIATION ON THE HYPOTHERMIA PREVENTION PROCESS IN NEWBORNS AT CLINIC PRATAMA SHAQI SLEMAN YOGYAKARTA - Pratiwi, Fika; husna, fauzul (LPPM STIKES Mataram, 2025)
Background : Early Breastfeeding Initiation (IMD) is the process of breastfeeding babies within 1 hour after the baby is born (WHO, 2018). Early Breastfeeding Initiation (IMD) can reduce the Infant Mortality Rate (AKB) caused by hypothermia (decrease in body temperature). The prevalence of the percentage of Early Breastfeeding Initiation (IMD) implementation in the world, according to UNICEF, is less than half of newborns, 47% are breastfed within 1 hour of birth. Meanwhile, the prevalence of the implementation of Early Breastfeeding Initiation (IMD) in Indonesia has not entirely reached the set target. In 2020, the target of IMD coverage in Indonesia is 54%. Objective: To find out the overview of the implementation of early breastfeeding initiation on the hypothermia prevention process in newborns at the Shaqi Sleman Primary Clinic Yogyakarta in 2023. Research Method : The method used in this study is a quantitative descriptive cross-section research design with a Secondary Data Analysis (ADS) approach. The sample method is a total sampling of 106 data. Research Results : This study shows that early initiation of breastfeeding can prevent hypothermia in newborns based on the sex of 62 females (58.5%) and 44 males (41.5%). In the <3 99 (93,4%) dan >5 it was 7 people (6.6%). At a body temperature of 36.5°C – 37.5°C 106 people (100%), hypothermia <35°C (0%) dan hipertemi >37.5°C (0%). In the division of hypothermy, 106 people (100%) were not hypothermic, 0 people (0%) had mild hypothermia, 0 people (0%) had moderate hypothermia and 0 people (0%) had severe hypothermia. In the administration of colostrum, all babies were given colostrum 106 people (100%) and non-colostrum was 0 people (0%). Conclusion : Early initiation of breastfeeding (IMD) can affect the body temperature of newborns so that in newborns at the Shaqi Primary Clinic there are no babies who have hypothermia. Keywords : Early Breastfeeding Initiation (IMD), Hypothermy, Newborn.